Mindfulness and its Relationship to Time Management (Field Study on Female Kindergarten Teachers in Ha'il City- Kingdom of Saudi Arabia) - Elsiddig, Fatma Mohamed Elkhier; Mahrous, Ghada Kamal (Journal of Educational and Psychological Sciences, 2020)
The aim of this research is to uncover the general trend of mindfulness and time management among female kindergarten teachers at Hail – Saudi Arabia. Likewise, the research aimed at knowing the correlation between mindfulness and time management, besides the differences in these two variables among the teachers in accordance to their marital status. The descriptive method was adopted. For data collection Mindfulness Scale designed by Abdullah (2013), and Time Management Scale designed by Azahrani (2010) were applied. The sample size was 102 female kindergarten teachers chosen in the simple random way. The research resulted in the following statistically significant results: mindfulness and time management are characterized by being positive, and there is a perpetual correlation between them; there is a difference between the teachers in mindfulness in favor of the married, while there is no difference between them in time management according to their marital status. Training programs on mindfulness and its applications has been recommended, besides some future researches has been suggested.
Keywords: mindfulness; time management; marital status; female kindergarten teachers